Chromospheric Modeling of the Active M3V Star G 80–21 with RH1.5D - Liu, Shuai; Wei, Huigang; Shi, Jianrong; Li, Wenxian; Han, Henggeng; Liu, Jifeng; Yang, Shangbin (The Astrophysical journal, 2024)
This study investigates the active regions of the M3.0V star G 80–21 using the observed data from the CARMENES project with synthetic spectra generated by the RH1.5D radiative transfer code. The CARMENES project aims to search for exoplanets around M dwarfs using high-resolution near-infrared and optical echelle spectrographs. By comparing the observed data and models for the chromospheric lines of H α and the bluest Ca ii infrared triplet line, we obtain the best-fit models for this star. The optimal fitting for the observed spectrum of G 80–21 is achieved by employing two active areas in conjunction with an inactive region, with a calcium abundance of [Ca/H] = −0.4. This combination successfully fits all the observed data across varying ratios. The minor active component consistently comprises approximately 18% of the total (ranging from 14% to 20%), which suggests that the minor active component is likely located in the polar regions. Meanwhile, the major active component occupies a variable proportion, ranging from 51% to 82%. Our method allows for the determination of the structure and size of stellar chromospheric active regions by analyzing high-resolution observed spectra.